STRATEGI MEDIA KOMUNIKASI VISUAL SEBAGAI UPAYA MEMBANGUN KESADARAN TENTANG CABIN FEVER BAGI REMAJA DI JAKARTA (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2022)
The Covid-19 Pandemic around Indonesia causes a big impact for those who are required to have outdoor activities. Besides economics affected by the pandemic, education is also affected due to the changes in teaching and learning, especially for the teenager who needs an education. This pandemic also causes some new rules from the government called Pembatasan Sosial Berskala Besar (PSBB) that makes people have to do their activities at home. This condition triggers some unusual feeling known as cabin fever. Cabin fever is a term to show a feeling of sadness, loneliness, fear, boredom, confusion, and depression excessively. Needs to know that cabin fever is not a mental disorder or mental illness either. However, the impact and symptoms that people experience can be harmful if they do not take action immediately.  Furthermore, cabin fever is not applied to people who look at this positively and do activities that are useful for them or for those whom doing some exercises, looking for new hobbies, maintaining good eating habits, and doing other useful activities. The methods of this research is a focus group to discuss and interview teenagers in Jakarta with the age range between 14-16 years old. These interviews are used virtual meetings because it is not possible did face to face interviews during pandemic. The purpose of this research is to find a media strategy for visual communication as an effort to build awareness about cabin fever among teenagers in Jakarta.